2016
DOI: 10.1080/17425255.2016.1192127
|View full text |Cite
|
Sign up to set email alerts
|

NAT2 polymorphisms and risk for Parkinson’s disease: a systematic review and meta-analysis

Abstract: Despite several recent meta-analyses showing an association between several polymorphisms in genes related with detoxification mechanisms such as cytochrome P4502D6 (CYP2D6), and glutathione transferases M1 and T1 (GSTM1, and GSTT1), data on NAT2 gene polymorphisms obtained from the current meta-analysis do not support a major association with PD risk, except in Asian populations. However, data from many studies are incomplete and therefore insufficient data exists to draw definitive conclusions. Several studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
(145 reference statements)
0
5
0
Order By: Relevance
“…Several other studies, however, failed to find an association (Dupret et al, 1999;Harhangi et al, 1999;Maraganore et al, 2000;Nicholl et al, 1999;van der Walt et al, 2003). Offering a more comprehensive overview, a meta-analysis by Jiménez-Jiménez et al (2016) revealed no significant association between the NAT2 slow acetylator phenotype and Parkinson's disease within Caucasian populations. Their analysis, however, revealed a strong relationship for Asian populations.…”
Section: H Nats and Neurodegenerative Diseasementioning
confidence: 98%
See 2 more Smart Citations
“…Several other studies, however, failed to find an association (Dupret et al, 1999;Harhangi et al, 1999;Maraganore et al, 2000;Nicholl et al, 1999;van der Walt et al, 2003). Offering a more comprehensive overview, a meta-analysis by Jiménez-Jiménez et al (2016) revealed no significant association between the NAT2 slow acetylator phenotype and Parkinson's disease within Caucasian populations. Their analysis, however, revealed a strong relationship for Asian populations.…”
Section: H Nats and Neurodegenerative Diseasementioning
confidence: 98%
“…In a pioneering study, Bandmann et al in 1997 highlighted a higher incidence of the NAT2 acetylator phenotype in patients with familial Parkinson's disease when compared to controls (Bandmann et al, 1997). Their finding spurred a series of subsequent investigations, and numerous studies have supported the association by reporting a heightened incidence of slow acetylators in cases of sporadic and early-onset Parkinson's disease across various ethnicities (Agúndez et al, 1998;Bandmann et al, 1997;Bandmann et al, 2000;Bialecka et al, 2002;Borlak and Reamon-Buettner, 2006;Chan et al, 2003;Chaudhary et al, 2005;Jiménez-Jiménez et al, 2016;Pandi et al, 2020;Singh et al, 2010;Tan et al, 2000). Several other studies, however, failed to find an association (Dupret et al, 1999;Harhangi et al, 1999;Maraganore et al, 2000;Nicholl et al, 1999;van der Walt et al, 2003).…”
Section: H Nats and Neurodegenerative Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…One such is the drugs and xenobiotics detoxification mechanisms pathways, in which a mice MPTP model of PD study showed that a polymorphism in cytochrome P450 family two subfamily D member 6 ( CYP2D6 ) caused susceptibility to PD (Jiménez-Jiménez et al, 1991 ). Following that, others have shown that some of these detoxification genes, GSTM1, GSTT1 , and NAT2 have been implicated in PD with controversial associations (Wang and Wang, 2014 ; Jiménez-Jiménez et al, 2016a ). Importantly, CYP2D6 and NAT2 genes have been shown exclusively to be associated with EOPD (Agúndez et al, 1995 ; Agundez et al, 1998 ), implying that these detoxification genes would have be suitable as EOPD biomarkers.…”
Section: Microrna Regulatory Network In Parkinson Diseasementioning
confidence: 99%
“…The second goal of this review is to discuss the potential of machine learning approaches, which could allow to better quantify complex phenotypes and to move beyond disease understanding towards a better personalized treatment of PD in the future. While previous reviews focused on the genetic architecture of PD and discuss associated risk factors ( Billingsley et al, 2018 ), gene-specific polymorphisms ( Jiménez-Jiménez et al, 2016 ), gene-gene and gene-environment interactions ( Singh et al, 2014 ; Dunn et al, 2019 ), our review has thus a distinguishable methodological focus.…”
Section: Introductionmentioning
confidence: 99%